Online political participation practices of Latin American youth - Torres Gastelú, Carlos Arturo (IE Revista de Investigación Educativa de la REDIECH, 2021)
Perception study on online political participation practices carried out by young people when connected to the Internet. The document shows the similarities and differences in the perception of university students, and between groups of countries. A quantitative approach was chosen through the application of a survey made up of 16 items. The study involved 2,810 Latin American university students (1,713 from Mexico, 651 from Colombia and 446 from Peru). Data analysis was performed using descriptive and inferential statistics. The results indicate that there are significant differences in young people’s perceptions of online political participation practices, both in the forms of political activism they carry out on the Internet and in their attitudes towards the role of online participation. However, in the comparison between groups of countries, similarities were detected in most of the items related to political activism on the Internet. Regarding the attitude of young university students towards the role of online participation, no similarities were found between the countries of Mexico, Colombia and Peru.